(untitled) (ARQUISUR Revista, 2024)
In the city of San Miguel de Tucumán, Argentina, there are 27 public buildings operating as primary health care centers (CAPS, by its initials in Spanish). Previous studies have shown that the thermal performance of their envelope is poor and leads to a very intensive use of active air conditioning systems. This work analyzes the energy consumption of these CAPS and aims to find a correlation between this, the outside air temperature and the main formal construction characteristics. For that purpose, the sample consisted of 14 representative cases, considering a previous census of the characteristics of those centers and a two-year period along 2022 and 2023. This analysis shows that the most representative item of energy consumption in CAPS is air temperature conditioning. Further research will be intended to propose measures aimed at reducing energy consumption by improving the technological features of building envelopes.